1996
DOI: 10.1021/tx950145x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Purified and Membrane-Bound Flavin-Containing Monooxygenase 1 by (N,N-Dimethylamino)stilbene Carboxylates

Abstract: (E)-[2-(4-(Dimethylamino)phenyl)vinyl]benzenes bearing a nitrile or carboxyl group in the 2', 3', or 4' position were synthesized and tested for substrate activity with purified pig liver flavin-containing monooxygenase (FMO1). Although the nitrile derivatives were too insoluble to saturate the catalytic site at pH 7.4, they appeared to be substrates with K(m)'s somewhat above their maximum solubility (approximately equal to 0.1 mM) in the assay medium. Of the three carboxylic acid analogs, (E)-4-[2-(4(dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…13 Such a “bold” catalytic strategy is consistent with the biodegradative role of the liver FMOs, which hydroxylate literally hundreds of structurally variable nucleophiles including amines, thiols, and halogenated compounds. 2,9 The FMOs are constitutively expressed; the FAD-OOH forms and simply persists until intercepted by a substrate. Continuous delivery of substrates to the liver minimizes the steady release of H 2 O 2 from FAD-OOH that otherwise would occur.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Such a “bold” catalytic strategy is consistent with the biodegradative role of the liver FMOs, which hydroxylate literally hundreds of structurally variable nucleophiles including amines, thiols, and halogenated compounds. 2,9 The FMOs are constitutively expressed; the FAD-OOH forms and simply persists until intercepted by a substrate. Continuous delivery of substrates to the liver minimizes the steady release of H 2 O 2 from FAD-OOH that otherwise would occur.…”
mentioning
confidence: 99%
“…Flavin-containing monooxygenases (FMOs) catalyze the oxygenation of diverse small organic molecules using O 2 , NADPH, and the flavin adenine dinucleotide (FAD) cofactor. , Genome sequencing has shown this family of enzymes to be widespread in bacteria, fungi, plants, and animals, though the mammalian FMOs are the only ones to have received significant prior attention. Like the cytochrome P450s, the mammalian liver FMOs are involved in the degradation of xenobiotics. FMOs from other sources, by contrast, appear to be primarily involved in the biosynthesis of diverse and important natural products.…”
mentioning
confidence: 99%
“…reported that 2,3,7,8‐tetrachlorodibenzo‐ p ‐dioxin highly induced FMO2 and FMO3 in the mouse in an aryl hydrocarbon receptor‐dependent manner . Only a few potent competitive inhibitors of FMOs such as, indole‐3‐carbinol (I3C), ( N , N ‐dimethylamino) stilbene carboxylates and 3,3′‐diindolylmethane (DIM) have been reported . Most of the apparent FMO inhibition is due to alternate substrate competitive inhibition where a good nucleophile competes with the drug for FMO oxygenation.…”
Section: Introductionmentioning
confidence: 99%